Microbial diversity in bioformulations of natural farming - Ranjan, Ravi Kant; Thakuria, Dwipendra (Umiam : CPGSAS, CAU, 2024)
he eco-friendly farming like organic and natural farming practices are increasingly becoming more prevalent and holds enormous promise from a business, social, and environmental standpoint. Although there is a progression of ideas from the past to the present, in natural farming practices, the application of Vedic formulations like Beejamrutha (BJ) and Jeevamrutha (JV) is frequently cited as having a good impact on crop development and yield. However, there is a dearth of research on the taxonomic diversity of microorganisms found in these biocultures. This study analyzed the microbial diversity in JV formulations using Marker gene (16S rRNA) based metagenomics studies. Four JV formulations were: 1. Original JV formulation, hereafter referred as JV(O), 2) JV(O)+BF (biofertilizer), 3) Modified JV, JV(M), and (JV(M)+BF. The functional microbial counts and microbial diversity was assessed after 7th day after incubation (DAI). A field trial on mung bean crop was performed by allocating 6 treatment combinations: 1. Control, 2. BJ, 3. JV(O), 4) JV(O)+BF, 5) JV(M), and 6) (JV(M)+BF in 4 replicated blocks using Randomized Block Design (RBD). Azospirillum was the highest in JV(O)+BF (7.61 Log CFU/ml) at 7th DAI. Rhizobium (7.76 Log CFU/ml) and Phosphate solubilizing bacteria (PSB) also reached peaked counts up to 7.75 Log CFU/ml in JV(O)+BF. Zinc solubilizer (6.90 Log CFU/ml) were the highest in JV(M)+BF at 15th DAI. Microbial diversity analysis at day one and 7th DAI showed dominance of phylla Firmicutes and Proteobacteria, and Genus, Lactobacillus, Streptococcus and Clostridium. Besides, the presence of Euryarchaeota, Bacteriodetes, and unclassified microorganisms in Jeevamrutha among others demonstrated the complexity of microbial diversity. Genus Leuconostoc dominated initially but decreased at 7th DAI, with Lactobacillus and Streptococcus increasing, particularly in JV(O)+BF and JV(M)+BF. Field trials showed differences in biological growth of green gram, with JV(M)+BF performed better in terms of plant growth parameters, root biomass, nodule number and concentration of nutrient (N, P, K and Zn) as compared to the other treatments. In conclusion, this study for the first time clearly depicted that JV formulation possessed taxonomically diverse microbial community and such microbial community could be altered by modifying the protein sources use in preparation of biocultures.
Includes bibliographical references.